(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the economic aspects of increasing the efficiency of raw material supply in the cotton-textile clusters of Uzbekistan. The trends in the development of cotton-textile clusters in the country, production volumes, labor productivity, export indicators, as well as the dynamics of raw materials and material costs are analyzed.